Maternal residential pesticide use and risk of childhood leukemia in Costa Rica. Issue 6 (26th April 2018) - Hyland, Carly; Gunier, Robert B.; Metayer, Catherine; Bates, Michael N.; Wesseling, Catharina; Mora, Ana M.
Abstract : Evidence suggests that early‐life exposure to pesticides inside the home may be associated with childhood leukemia, however data from Latin American countries are limited. We examined whether self‐reported maternal residential pesticide use and nearby pesticide applications–before and after child's birth–were associated with acute lymphoblastic leukemia (ALL) in the Costa Rican Childhood Leukemia Study (CRCLS), a population‐based case‐control study (2001‐2003). Cases ( n = 251 ALL) were diagnosed between 1995 and 2000 (age <15 years at diagnosis) and were identified through the Costa Rican Cancer Registry and National Children's Hospital. Population controls ( n = 577) were drawn from the National Birth Registry. We fitted unconditional logistic regression models adjusted for child sex, birth year, and socioeconomic status to estimate the exposure‐outcome associations and also stratified by child sex. We observed that self‐reported maternal insecticide use inside the home in the year before pregnancy, during pregnancy, and while breastfeeding was associated with increased odds of ALL among boys [adjusted Odds Ratio (aOR) = 1.63 (95% confidence interval [95% CI]: 1.05–2.53), 1.75 (1.13–2.73), and 1.75 (1.12–2.73), respectively. We also found evidence of exposure‐response relationships between more frequent maternal insecticide use inside the home and increased odds of ALL among boys and girls combined. Maternal report of pesticide applications on farms or companies near the home during pregnancy and at any time period were also associated with ALL. Our study in Costa Rica highlights the need for education to minimize pesticide exposures inside and around the home, particularly during pregnancy and breastfeeding. Abstract : What's new? Costa Rica has one of the highest incidence rates of childhood leukemia worldwide. Pesticide use is widespread there, raising questions about whether pesticide exposure is in part responsible for the country's elevated childhood leukemia incidence. Here, acute lymphoblastic leukemia (ALL) in Costa Rican boys was associated with maternal insecticide use in the home as well as with pesticide spraying on nearby farms before and after the child's birth. Among both boys and girls, ALL risk increased in association with frequency of maternal in‐home insecticide use. The results offer insight into possible areas of intervention to reduce childhood leukemia risk.